Peranan hujan terhadap dinamika hara di bawah tegakan eucaliptus urophylla S.T. Blake dan Acacia mangium wild - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
ABSTRAK three kinds of cover area and the rainfall take pThe purose of this research is to study about the balance between nutrient input and output under Eucalyptus urophylla and Araria mangium stands with regard to rainfall, and hydrological aspect at the two stands. This research was conductedon 3.5 year old stands in Wanagama I Gunung Kidul at 10% slope. The nutrient input carried by the rainfallto the soil under the standfloor and output carried by the surface runoff were measured, based on the para meters of N, P, and K elements. Based on nutrient aspect, the result showed that from 5 time observations with the average rainfall 37.50 q 5.26 mm, the nutrient input to the soil under the two stands was greater than the nutrient output carried out by surface runoff, while at the bare area showed the opposite result. As far as the hydrological aspect is concerned, the result showed that as long as 75 days rainfall with the average rainfall 21.54 q 25.84 mm it was found the significant differences in the throughfall, step flow, and canepy interception at the two stands but not in litter interception and surface runoff. Compared with the bare area, the surface runoff under the two stands was much smaller. The two kinds of stand and the rainfall take part in giving contribution to the amount of throughfall, stemflow, and canopy interception with linear pattern, and also to the amount of litter interception with logarithmic pattern. The three kinds of cover area and the rainfall take part in giving contribution to the amount surface runoff, although it is relatively a little.